Legalitas nikah paksa perspektif hukum positif dan hukum Islam - Andini, Dwi (Maliki Interdisciplinary Journal, 2024)
Marriage is a sacred, sacred process that connects two individuals with a bond that is based on positive law in Indonesia. However, in Indonesia there are still many marriages without any element of affection due to coercion in the practice of marriage which is called forced marriage. Several factors drive forced marriage, namely economic factors, cultural factors, legal awareness factors, and legal substance factors. This practice of forced marriage is carried out by a guardian. Although a guardian has the right to marry the bride, a guardian is not allowed to force the woman to get married unless she agrees. From a legal and formal perspective, forced marriage in Indonesia is a criminal act of sexual violence in several articles, one of which is Article 10(1)(e) number 12 of the Sexual Offenses Law of the Republic of Indonesia 2022.